Pengaruh Motivasi Wirausaha, Lingkungan Keluarga dan Orientasi Kewirausahaan Terhadap Minat Berwirausaha - Dianingrum, Sinta; Hidayati, Nur; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to find out and analyze how much influence entrepreneurial motivation, family environment and entrepreneurial orientation have on entrepreneurial interest. The population in this study were youth entering late adolescence and early adulthood in Kebobang Village. The data collection method in this research used a questionnaire with a sample size determined using the Slovin formula and the results obtained were 83 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and coefficient of determination test (R2). The results of this research simultaneously show that the influence of entrepreneurial motivation, family environment and entrepreneurial orientation influences entrepreneurial interest. Partially, Entrepreneurial Motivation and Entrepreneurial Orientation influence Entrepreneurial Interest, while the Family Environment has no influence on Entrepreneurial Interest. Keywords: Entrepreneurial Motivation, Family Environment, Entrepreneurial Orientation and Entrepreneurial Interest.